2020
DOI: 10.1021/acs.organomet.0c00104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of an Oxo-Centered Homotrimetallic Uranium(IV)–Cyclobutadienyl Dianion Complex

Abstract: Reaction of [Li 2 {C 4 (SiMe 3 ) 4 }(THF) 2 ] (1) with [U(η 5 -C 5 Me 5 )I 2 (THF)] (2) produced the oxo-centered homotrimetallic uranium−pentamethylcyclopentadienyl complex [{U(η 5 -C 5 Me 5 )(μ-I) 2 } 3 {μ 3 -O}{Li(THF) 3 } 0.5 ] 2 [Li(THF) 4 ] (3) as the only isolable product in a very low yield. In contrast, reaction of 2 with [Mg{C 4 (SiMe 3 ) 4 }(THF) 3 ] (4) produced the oxo-centered homotrimetallic uranium(IV)−cyclobutadienyl complex [{U(C 4 [SiMe 3 ] 4 )(μ-I) 2 } 3 {μ 3 -O}][Mg(THF) 6 ] (5). The solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 66 publications
0
38
0
Order By: Relevance
“…The average cyclobutadienyl C 4 -ring C-C distances in 1 are identical at 1.481(8) A, and statistically indistinguishable from the analogous metric for A (1.488(17) A). [8][9][10] The displacement of the cyclobutadienyl silyl substituents in 1, out of the plane of the C 4 -ring away from the respective thorium centres, is notable due to their asymmetry. Opposing silyl groups are displaced by similar distances to each other, but each pair is quite different to the other.…”
Section: Crystallographic Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The average cyclobutadienyl C 4 -ring C-C distances in 1 are identical at 1.481(8) A, and statistically indistinguishable from the analogous metric for A (1.488(17) A). [8][9][10] The displacement of the cyclobutadienyl silyl substituents in 1, out of the plane of the C 4 -ring away from the respective thorium centres, is notable due to their asymmetry. Opposing silyl groups are displaced by similar distances to each other, but each pair is quite different to the other.…”
Section: Crystallographic Characterisationmentioning
confidence: 99%
“…6,7 Very recently, the uranium(IV)-cyclobutadienyl half sandwich pianostool complex [U{C 4 (SiMe 3 ) 4 }(BH 4 ) 3 ][Li(THF) 4 ] (A) was reported, 8 and shortly aer that four uranium(IV)-cyclobutadienyl complexes [U{C 4 (SiMe 3 ) 4 }(BH 4 ) 3 ][Na(12-crown-4)], 9 [U{C 4 -(SiMe 3 ) 4 }(BH 4 ) 2 (m-BH 4 ){K(THF) 2 }] 2 , 9 [U(BH 4 ){C 4 (SiMe 3 ) 4 }{k 3 -C 4 H(SiMe 3 ) 3 -k-(CH 2 SiMe 2 )}][Na( t BuOMe) 3.6 (THF) 0.4 ], 9 and [{U(C 4 [SiMe 3 ] 4 )(m-I) 2 } 3 {m 3 -O}][Mg(THF) 6 ] were disclosed. 10 These six uranium-cyclobutadienyl complexes constitute all actinidecyclobutadienyl chemistry to date, in stark contrast to the plethora of reported f-element h n -carbocyclic C 5-9 complexes. 11 Thus, a thorium-cyclobutadienyl complex of any kind is conspicuous by its absence, but realising such a target would provide comparisons between uranium and thorium and provide further insight into actinide-cyclobutadienyl bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The average U-C distance in 9 is 2.574(7) Å;; statistically indistinguishable from that measured for halfsandwich complex 5 (2.513(17) Å), despite the differing uranium coordination environments in the two complexes. [22,31] As found for all crystallographically characterised uraniumtetra(trimethylsilyl)cyclobutadienyl complexes, in 9 the cyclobutadienyl silyl substituents bend out of the plane of the C4ring, away from the coordinated uranium centre. These displacements range from 0.478(13) to 0.652(12) Å, which is a broader range than found for 5.…”
Section: A Homotrimetallic Uranium(iv)-cyclobutadienyl Complexmentioning
confidence: 78%
“…[32] However, it was found that reaction of [U(η 5 -C5Me5)I2(THF)] with [Mg{C4(SiMe3)4}(THF)2] (1Mg) in benzene led to the formation of the oxo-centred homotrimetallic uranium(IV)-cyclobutadienyl complex [{U(C4[SiMe3]4)(μ-I)2}3{μ3-O}][Mg(THF)6] (9) in 19% crystalline yield (Scheme 5). [24,31] The reasons for the divergent reactivities displayed by 1Li and 1Mg towards [U(η 5 -C5Me5)I2(THF)] are unclear, but are perhaps a consequence of the differing Lewis acidities of the two s-block metals. As determined by X-ray diffraction, complex 9 features three uranium(IV) ions in a trigonal planar arrangement around a central μ3-oxo ligand, with two bridging μ-iodide ligands between each pair of uranium centres.…”
Section: A Homotrimetallic Uranium(iv)-cyclobutadienyl Complexmentioning
confidence: 99%
See 1 more Smart Citation